Diversification of transcriptional modulation: Large-scale identification and characterization of putative alternative promoters of human genes - Kimura, Kouichi; Wakamatsu, Ai; Suzuki, Yutaka; Ota, Toshio; Nishikawa, Tetsuo; Yamashita, Riu; Yamamoto, Jun-ichi; Sekine, Mitsuo; Tsuritani, Katsuki; Wakaguri, Hiroyuki; Ishii, Shizuko; Sugiyama, Tomoyasu; et al. (Genome Research, 2006)
By analyzing 1,780,295 5′-end sequences of human full-length cDNAs derived from 164 kinds of oligo-cap cDNA libraries, we identified 269,774 independent positions of transcriptional start sites (TSSs) for 14,628 human RefSeq genes. These TSSs were clustered into 30,964 clusters that were separated from each other by more than 500 bp and thus are very likely to constitute mutually distinct alternative promoters. To our surprise, at least 7674 (52%) human RefSeq genes were subject to regulation by putative alternative promoters (PAPs). On average, there were 3.1 PAPs per gene, with the composition of one CpG-island-containing promoter per 2.6 CpG-less promoters. In 17% of the PAP-containing loci, tissue-specific use of the PAPs was observed. The richest tissue sources of the tissue-specific PAPs were testis and brain. It was also intriguing that the PAP-containing promoters were enriched in the genes encoding signal transduction-related proteins and were rarer in the genes encoding extracellular proteins, possibly reflecting the varied functional requirement for and the restricted expression of those categories of genes, respectively. The patterns of the first exons were highly diverse as well. On average, there were 7.7 different splicing types of first exons per locus partly produced by the PAPs, suggesting that a wide variety of transcripts can be achieved by this mechanism. Our findings suggest that use of alternate promoters and consequent alternative use of first exons should play a pivotal role in generating the complexity required for the highly elaborated molecular systems in humans.
10.1101/gr.4039406